Integration of the Porter Five Forces Model and the House of Risk from a Service Performance Perspective to Increase Competitiveness (Case Study at UNIBA Madura) - Wahyuningtias, Novi; Basuki, Minto (Universitas Trunojoyo Madura, 2023)
In managing a company, whether manufacturing or service, it will never be free from risks, including educational institutions. The increasingly fierce competition in creating a competent and quality educational institution begins with how to get new students. This certainly never escapes risk management. Bahaudin Mudhary Madura University tries to reduce the level of risk as little as possible in order to improve the quality of existing education and compete in getting new students with other universities in Madura, especially Sumenep. Registration of new students is the initial activity in higher education because it requires innovation and creative ideas in recruiting prospective students. This research uses the House of Risk method to prioritize risk agents and determine the most effective actions against risks that occur and is integrated with Porter's five forces to describe the framework as an analysis of business strategy development or the competitive environment that contributes to competitiveness and competitive advantage. The results of the analysis based on Porter's Five Forces model show that for the bargaining power of new student admissions at UNIBA Madura, there are several things that UNIBA Madura must do to attract and increase the interest of new students, namely increasing information and promotion of UNIBA Madura. The results of the first phase of HOR showed that the most dominant sources of risk at UNIBA Madura were the cost of developing a large campus, the lack of interest of doctoral lecturers in teaching, and the number of relationships was still small and based on phase 2 of HOR, it was found that risk mitigation strategy actions to minimize the risks that occurred were by collaborate with foundations/institutions related to funding so that UNIBA Madura can minimize the risk of accepting new students.